PENGARUH ENTERPRISE RISK MANAGEMENT TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERASI - Nisa Alisva Anggreini; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2023)
Enterprise Risk Management (ERM) is a framework for managing corporate risk in a comprehensive, structured and integrated manner. Value for the company will be created and protected through the use of ERM. Investors have their own considerations regarding the value of the company when making decisions to invest. Investors can learn more about the company's risk management practices through the publication of an annual report that highlights the application of ERM in risk management. The information obtained by investors will be of added value to the company not only for now but for long term prospects. This study aims to determine the effect of ERM on firm value. The research was conducted in the banking sector listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. This study also uses a moderating variable in the form of managerial share ownership. In addition, it also uses control variables consisting of company size and leverage. The results of the study show that ERM has a significant positive effect on firm value. For the moderation of managerial share ownership, the interaction of ERM and managerial share ownership has no significant effect on firm value.